Experimental study of a PA66 solid polymer in the case of cyclic shear loading - Bles, G.; Gadaj, S.P.; Nowacki, W.K.; Tourabi, A. (Archives of Mechanics, 2002)
Experimental mechanical results concerning cyclic shear tests without lateral force and simple shear tests with measurement of temperature, performed on sheet samples of PA66 polyamide, are presented. These tests are performed using special shear devices, attached to a classical tensile testing machine. The aim of our work was the examination of thermomechanical characteristics of solid polyamide during shear loading. This study allowed us to analyse the changes of the stress and strain characteristics, shear modulus, ratcheting, relaxation effects and thermomechanical effects.